Aggregate resources inventory of Ontario - Dale Scott (Canadian Institute of Mining, Metallurgy and Petroleum, 1982)
"The Aggregate Resources Inventory Program was initiated 10 produce reports which assess the aggregate resources of municipalities designated under the Pits and Quarries Control ACI, 1971.Each report consists of three copies accompanied by a text. The text describes the local mineral aggregate resources, extractive activity and characteristics of the ""Selected Deposits"". The first map shows the known sand and gravel resources and their quality. The second map indicates selected sand and gravel resources of primary, secondary and tertiary significance. The third map indicates both bedrock resources and bedrock areas suitable f or extraction. These maps and the text are prepared in a formal suited for use by planning personnel.Recently, the Aggregate Resources Inventory Program has undergone evolutionary changes. New sources of data are being utilized in the inventory reports; in particular, detailed field assessment by inspecting, sampling, drilling and backhoe pitting. Liaison and joint assessment with district and regional Mineral Resources staff of the Ministry of Natural Resources, and personnel of the Ministry of Transportation and Communications, are key components of the Program.Twenty-two reports were available to the public as of December 1980, with a further thirty-six awaiting publication. Our present production rate is 3.5 reports per month. The reports appear to be well accepted by the municipalities and have proven effective in conserving prime aggregate resource areas.IntroductionThe urbanization of Southern Ontario has resulted in a major increase in the production of industrial minerals, such as sand, gravel, clay, shale, gypsum and stone, for use as cru shed aggregate, building stone, lime and cement.Although mineral aggregate deposits are plentiful in Southern Ontario, they are fixed-location, non-renewable resources. The potential for extractive development is usually greatest in urban fringe areas where land-use competition is extreme. Comprehensive planning and resource management strategies are required to make the best use of available resources, especially in those areas experiencing rapid development. Such strategies must be based on a sound knowledge of the total mineral aggregate resource base at both local and regional levels."